Concerning second main Brawer’s theorem - Gres , P. G. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The inverse of the well-known Brauer formula is given, which is a consequence of his second main theorem. The formula can be applied to an evaluation of values of characters of local subgroups. Moreover, if b is a block of СG (π), B is a block of a group G, then a method is found to check the equality bG = В.